Discrete RNA–DNA hybrid cleavage by the EXD2 exonuclease pinpoints two rate‐limiting steps. (3rd November 2022) - Jia, Xinshuo; Li, Yanan; Wang, Teng; Bi, Lulu; Guo, Lijuan; Chen, Ziting; Zhang, Xia; Ye, Shasha; Chen, Jia; Yang, Bei; Sun, Bo
Abstract: EXD2 is a recently identified exonuclease that cleaves RNA and DNA in double‐stranded (ds) forms. It thus serves as a model system for investigating the similarities and discrepancies between exoribonuclease and exodeoxyribonuclease activities and for understanding the nucleic acid (NA) unwinding‐degradation coordination of an exonuclease. Here, using a single‐molecule fluorescence resonance energy transfer (smFRET) approach, we show that despite stable binding to both substrates, EXD2 barely cleaves dsDNA and yet displays both exoribonuclease and exodeoxyribonuclease activities toward RNA–DNA hybrids with a cleavage preference for RNA. Unexpectedly, EXD2‐mediated hybrid cleavage proceeds in a discrete stepwise pattern, wherein a sudden 4‐bp duplex unwinding increment and the subsequent dwell constitute a complete hydrolysis cycle. The relatively weak exodeoxyribonuclease activity of EXD2 partially originates from frequent hybrid rewinding. Importantly, kinetic analysis and comparison of the dwell times under varied conditions reveal two rate‐limiting steps of hybrid unwinding and nucleotide excision. Overall, our findings help better understand the cellular functions of EXD2, and the cyclic coupling between duplex unwinding and exonucleolytic degradation may be generalizable to other exonucleases. Synopsis: This study provides a dynamic understanding of the exonuclease activity of EXD2 toward RNA and DNA in double‐stranded forms. The discrete stepwise RNA–DNA hybrid cleavage of EXD2 reveals both duplex unwinding and nucleotide excision as rate‐limiting steps in nucleic acid degradation. The EXD2 exonuclease preferentially degrades RNA over DNA within RNA–DNA hybrids. EXD2 unwinds four base pairs of RNA–DNA hybrids prior to excising one nucleotide at a time. Nucleotide excision and duplex unwinding are two rate‐limiting steps in EXD2‐mediated double‐stranded nucleic acid cleavage. The frequent duplex rewinding impedes EXD2 from degrading DNA in double‐stranded forms. Abstract : EXD2 preferentially degrades RNA over DNA within hybrid duplexes, unwinding four basepairs before excising single nucleotides at a time.